2009 American Control Conference 2009
DOI: 10.1109/acc.2009.5159942
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of travel times and traffic emissions using model predictive control

Abstract: Abstract-In this paper we present a model-based traffic flow control approach to improve both traffic flow and emissions in a traffic network. A model predictive control (MPC) is implemented using a microscopic car-following traffic flow model and an average-speed-based emission model. We consider reduction of total time spent (TTS) and total emissions (TE) as performance measures of the control strategy. Moreover, with the help of simulations we illustrate that a traffic control strategy, particularly an MPC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…In addition, greenhouse gas emissions are higher during stop-and-go and congested traffic conditions than in free flow conditions. Zegeye et al (2010) used MPC approach to assess the impact of dynamic speed limit control in reducing CO 2 emissions, fuel consumption and travel time. Their study concluded that a reduction of Total Time Spent (TTS) alone could not meet the requirement of reducing emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, greenhouse gas emissions are higher during stop-and-go and congested traffic conditions than in free flow conditions. Zegeye et al (2010) used MPC approach to assess the impact of dynamic speed limit control in reducing CO 2 emissions, fuel consumption and travel time. Their study concluded that a reduction of Total Time Spent (TTS) alone could not meet the requirement of reducing emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…3. Improved throughput and environmental benefits: Since congestion is also associated with increased fuel consumption and emissions, the capability of VSL in improving traffic flow also results in environmental benefits (Zegeye et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Bai et al (2007) applied dynamic assignment techniques to compute emission from on-road vehicles. Zegeye et al (2009) proposed model predictive control to reduce travel time and emission at the same time. Li et al (2005) considered emission concentration standards provided by NAAQS as a constraint and determined the capacity of links.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, to minimize the CO 2 emission from the vehicles, the number of stops has large influence. However, since there is a trade-off between the total duration and the number of stops caused by traffic signals as reported in [3], the signal control policy that can minimize the duration of stops might not be efficient for reduction of the number of stops. A famous microscopic signal control method called RHODES [4] can be applied to minimize the CO 2 emission from the vehicles by replacing the objective function of the method with another function that evaluates the amount of exhaust gases.…”
Section: Introductionmentioning
confidence: 96%